Asymmetric dominance effect with multiple decoys for low- and high-variance lotteries - Oktay Sürücü; Sonja Brangewitz; Behnud Mir Djawadi (Bielefeld University, Center for Mathematical Economics (IMW), 2017)
The asymmetric dominance effect refers to the phenomenon according to which the choice probability of an alternative increases when an inferior alternative - the decoy - is included into the choice set. The objective of this experimental study is twofold. First, we investigate the asymmetric dominance effect on two-outcome lotteries with almost equal expected values. We find that the impact of a decoy on low-variance lotteries (LVLs) is much higher than on high-variance lotteries (HVLs). Second, we examine the asymmetric dominance effect in the presence of two decoys. While the asymmetric dominance effect persists when the choice set includes two decoys, the effect is not always further enhanced compared to the setting with one decoy and again much stronger for LVLs than for HVLs. Controlling for subjects' degrees of risk aversion, we find support for consistency between individual risk preferences and choice behavior among the lotteries. However, we observe decoy effects of equal strength irrespective of the subjects' degree of risk aversion. Thus, our analysis indicates that to a substantial extent the presence of decoys subtly makes decision-makers choose against their risk preferences by favoring lotteries that entail risks contrary to their elicited individual risk-taking profile.
urn:nbn:de:0070-pub-29106712
Keywords: C91; D12; D83; 330; Asymmetric dominance effect; decoy effects; multiple decoys; risk aversion; individual decision making; experimental economics